Shortened PQ interval in the differential diagnosis of Anderson-Fabry disease: a case report - P. D. Zlobina; A. A. Kalemberg; R. P. Myasnikov; M. S. Kharlap; O. V. Kulikova; E. A. Mershina; A. V. Tarasov; K. V. Davtyan (Российский кардиологический журнал, 2022)
In this article, we present a case of a patient with a late diagnosis of Fabry disease caused by a pathogenic variant in the GLA gene (p.1287_1288dup), who repeatedly attempted interventional treatment of Wolff-Parkinson-White Syndrome due to characteristic electrocardiographic pattern of ventricular preexcitation and paroxysmal arrhythmias. The proposed pathognomonic signs of the disease will ensure timely diagnosis and the appointment of specific treatment.